CYBERBULLYING: CONCEPT, FEATURES, AND INTERNATIONAL LEGAL STANDARDS FOR THE PROTECTION OF CHILDREN FROM CYBERBULLYING - Dilshod Shavkatovich Israilov (International Journal of Business, Law and Political Science, 2026)
Objective: This article provides a comprehensive analysis of criminal liability and sentencing for cyberbullying against children in the school environment. Method: It examines the concept and key features of cyberbullying, relevant international legal standards for child protection, as well as national legislation and challenges in legal qualification of such acts.  Results: Particular attention is paid to the individualization of punishment, taking into account the personality of juvenile offenders and the impact on child victims.  Novelty: Based on the research, the author proposes measures to improve criminal legislation, judicial practice, and preventive mechanisms aimed at ensuring effective protection of children's rights in the digital educational environment.